Cognitive engineering. Issue 1 (18th October 2012) - Wilson, Kyle M.; Helton, William S.; Wiggins, Mark W.
Abstract Cognitive engineering is the application of cognitive psychology and related disciplines to the design and operation of human–machine systems. Cognitive engineering combines both detailed and close study of the human worker in the actual work context and the study of the worker in more controlled environments. Cognitive engineering combines multiple methods and perspectives to achieve the goal of improved system performance. Given the origins of experimental psychology itself in issues regarding the design of human–machine systems, cognitive engineering is a core, or fundamental, discipline within academic psychology. WIREs Cogn Sci 2013, 4:17–31. doi: 10.1002/wcs.1204 Conflict of interest: The authors declare no conflict of interest. For further resources related to this article, please visit the WIREs website.